Aplikasi Metode Aktivasi Netron untuk Penetapan Mineral Selenium dalam Produk Suplemen Kesehatan - Titiek Martati; June Mellawati (Fakultas Farmasi Universitas Pancasila, 2005)
Recently, there are some health supplement products that are useful as an antioxidant in the market, and one of them is Selenium (Se) tablet. Therefore issue of falsification of drug due to the control of health supplement product become very important. In this research the determination of Se in health supplement tablet using neutron activation analysis has been carried out. Sample was irradiated using thermal neutron with 1013 neutron cm-?secondfluxes within 15 minutes, and based on n, y reaction 75Se isotope would be formed that could identified using Gamma spectrometer on 136, 264, and 279 keV energies. The result showed that neutron activation analysis method can analysis Se mineral that contained in health supplement tablet with accuracy ranged between 101.81 – 102.29 % and precision 99.02 -99.37%. The recovery test of Se mineral concentration to the labeled attached showed 105.79 - 116.66%, and this value was still in the recommended range according to the USP 28 (90 – 125%).